THE INFLUENCE OF LEARNING MOTIVATION AND DISCIPLINE ON STUDENTS' LEARNING ACHIEVEMENT OF CLASS X STUDENTS AT SMK PERDANA 1 SURABAYA - Aradina Mirza Dewi; Rohmah Kurniawati (Jurnal Ekonomi, 2023)
This study examines student motivation and academic performance at SMK Perdana 1 in Surabaya, Indonesia. Researcher questionnaires are their main data collection and distribution strategy. Quantitative research was done, and SPSS was used to analyze the data using multiple regression. The data showed that learning discipline and motivation both affect learning achievement.